Analysis of Residual Solvent Problems In Cooking Oil Packaging Products at PT X - Fadillah, Fakhri (Kreator, 2023)
The packaging printing production process cannot be separated from the problems that affect the product yield, and solvent residue is one of them. Quality control or quality control is needed in a business to achieve the desired results and minimize problems so that these products can be sold to customers. Product quality has several weaknesses, such as residual solvent, sealing and leaking. Apart from the disadvantages mentioned, the most important critical point is the high residual solvent content. The way to solve the problem at the critical point of remaining solvent is to clean the chamber, exos and chiller and increase the temperature of the chamber so that the evaporation of the remaining solvent remains, and gas chromatography examination to assist in sample verification. Based on the problems identified, product quality results at PT X can reduce problems in products with high solvent residues. PT X is a manufacturer, marketer and distributor of cooking oil products.